ANALISA HARMONISA PADA KARAKTERISTIK MOTOR INDUKSI TIGA PHASA - Ferry Rahmat Astianta Bukit (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
Three Phase Induction Motors are widely used in the industrial world, therefore induction motors are expected to operate normally according to the desired work characteristics. But can not be denied the existence of interference that can cause damage to work induction motor system that one of them is harmonics. The purpose of writing this article is to explain the working characteristics of three phase induction motor which generates harmonics and in operation also contains harmonics. The method used in the study analyzed the working characteristics of three phase induction motor which in its operation contains harmonics. The harmonic form is analyzed by using Fourier series representation. The results obtained from this study indicate that under operating conditions containing harmonics, the stator magnetic field generates a rotating harmonic field that produces a forward and backward mmf mmf. Another effect of this harmonic, is the incidence of harmonic torque which coincides with the fundamental torque produces vibration and noise which has considerable effect on the operation of three phase induction motors.